PEMBINAAN MODUL LATIHAN KENDIRI TAJWID RED-SIGN BAGI MENINGKATKAN PENGUASAAN TAJWID PELAJAR SEKOLAH MENENGAH HARIAN: THE DEVELOPMENT OF RED-SIGN TAJWID SELF LEARNING MODULE TO COMPREHEND TAJWID PRACTICES AMONG NATIONAL SECONDARY SCHOOL STUDENTS - Norwardatun Mohamed Razali; Siti Rosilawati Ramlan; Maisarah Saidin (Maʿālim al-Qurʾān wa al-Sunnah, 2022)
The effort of teaching al-Quran to childrens has been applied by parents as early as four years old. This effort continues in primary school since 7 to 12 years old with j-QAF syllabus in National Primary Schools and also additional KAFA classes in religious primary schools. However, the effectiveness of tajwid syllabus on students' ability to read al-Quran is still in unsatisfactory level. Among the factors which contribute to the weakness of students are incompetent teachers, less effective teaching and learning methods which further affect the ability to read al-Qur'an with tajwid when move to secondary school. The students who have reached the secondary school level need to be helped by looking at one of the factors contributing to this weakness, which is less effective teaching aids. This study aims to review the need of the development of tajwid self-learning modules to comprehend tajwid practices among National Secondary School Students. This study is a qualitative study which is collecting documentation from literature studies that touch on the skills of reciting the Qur'an. The results of this study found that the method of teaching Ilmu Tajwid and teaching aids need to be upgraded so that students can practice it independently at school and home. In conclusion, new teaching aids such as the Red Sign Tajwid Self-Training Module need to be developed to facilitate the process of imparting Ilmu Tajwid that can be used by student independently in class and home.